Fronteras - Marqués-Pascual, Joaquin (Comunicación y Medios, 2022)
Javier de Lucas, Javier Bauluz, Daniela Pastrana, Juan José Téllez y Nicolás Castellano. (2019). Fronteras. Madrid (España): Editorial Hispalibros SL. 156 páginas. ISBN: 9 8-84-17993-18-4